Fonologi Bahasa Perbedaan Alofon Bahasa Indonesia Dengan Bahasa Sunda - Syifa Nurjamilah; Sri Yulistiani Viranti; Moh. Naufal Mufid (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2023)
The purpose of this study was aimed at determining the difference between Indonesian allophones and Sundanese. in Indonesian, allophones are often associated with variations in the pronunciation of consonants and vowels, while in Sundanese these variations can include word forms and intonation patterns. The method used in this study uses qualitative methods by investigating the differences between Indonesian allophones and Sundanese so as to produce concrete data. Such as differences in vowel phonemes and consonant phonemes between Indonesian and Sundanese, differences in consonant allophones and vowel allophones, differences in the use of certain sounds, differences in intonation patterns and accents. With this research, it can produce data that can distinguish between Indonesian allophones and Sundanese allophones